Characterization of Colletotrichum lindemuthianum races infecting dry edible bean in North Dakota. Issue 1 (2nd January 2016) - Halvorson, Jessica M.; Lamppa, Robin S.; Markell, Samuel G.; Pasche, Julie S.
Abstract: Anthracnose, caused by the fungal pathogen Colletotrichum lindemuthianum (Sacc. & Magnus) Lams.-Scrib., is an economically important and damaging disease of dry bean ( Phaseolus vulgaris L.) that can cause large reductions in yield and seed quality. Yield losses can reach 100% when contaminated seed is used, large amounts of inoculum are present, and favourable weather conditions occur during the crop cycle. Although widespread losses to anthracnose have not been observed in North Dakota, the lack of host resistance and favourable environmental conditions could lead to substantial economic losses. Additionally, numerous races of this pathogen exist and the pathogen race structure has the ability to change over time. Of the several races detected in North Dakota from 2003 to 2009, race 73 was the most prevalent. The purpose of this study was to determine the pathogen race types of C. lindemuthianum collected from dry bean samples in North Dakota from 2012 to 2014. Based on the 33 isolates collected in 2012 and 53 isolates collected in 2014, race 73 continues to be the most common race of C. lindemuthianum in North Dakota. Races 9 and 72 were also identified; however, these pose little additional threat due to virulence pattern similarities with race 73.